Allelopathy of the Medicinal Plant Dregea volubilis (L.f.) Benth. ex Hook.f. and Its Phytotoxic Substances with Allelopathic Activity - Ei Han Kyaw; Arihiro Iwasaki; Kiyotake Suenaga; Hisashi Kato-Noguchi (Agronomy, 2022)
Allelopathic plants and their related phytotoxic chemicals have been explored as alternatives for environmentally friendly weed management. Dregea volubilis (L.f.) Benth. ex Hook.f., a woody vine, is well-known for its uses in various therapeutic treatments, and several bioactive compounds have been isolated from this species. However, to date, no phytotoxic substances from D. volubilis have been reported. Hence, in this research, we aimed to investigate the allelopathic effect of D. volubilis and characterize its phytotoxic substances. Extracts of D. volubilis exhibited significant inhibitory activity against the seedling growth of Italian ryegrass (Lolium multiflorum Lam.) and cress (Lepidium sativum L.). The extracts were purified through several chromatography steps, yielding two phytotoxic substances, and using spectroscopy, their structures were determined as dehydrovomifoliol and loliolide. The compounds inhibited the Italian ryegrass and cress seedlings with the I50 (concentrations needed for 50% inhibition) values ranging from 0.022 to 0.102 mM, for loliolide and 3.24–4.60 mM, for dehydrovomifoliol. These results suggest that both phytotoxic compounds might be responsible for the allelopathy of D. volubilis, and they may be released into the soil through the decomposition of the D. volubilis leaf and probably act as allelopathic active substances. Therefore, the extracts of D. volubilis and its related phytotoxic compounds may be applied as biological agents for controlling weeds.